Tales from a not-so-secret crush catastrophe - e uthor; Russell, Nikki; Russell, Erin (New York : Aladdin, 2017)
As Nikki plans how she's going to spend her summer, things get more complicated after she starts hanging out with a visiting student.
5.3
3-6
680L
Keywords: Teenage girls -- Fiction; Middle schools -- Fiction; Friendship -- Fiction; Infatuation -- Fiction; Teenage girls -- Fiction; Middle schools -- Fiction; School stories; Friendship -- Fiction; Infatuation -- Fiction; Diary fiction